Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10661-008-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of marine sponge, Haliclona tenuiramosa as bioindicator to monitor heavy metal pollution in the coasts of Gulf of Mannar, India

Abstract: The results of the present research study indicate that the heavy metal accumulation in the marine sponges provide evidence as an excellent bioindicators for monitoring heavy metal pollution between near and offshore environments of Mandapam coast of "Gulf of Mannar (GoM), India". The heavy metal concentrations in sea water and accumulation in the tissues of Haliclona tenuiramosa were analyzed by ICP-MS (inductively coupled plasma-mass spectrometry). The concentrations of metals in the coastal waters of nearsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 18 publications
1
12
0
4
Order By: Relevance
“…Hence, the species distribution patterns, morphological and anatomical variations within the species may influence the production of different kinds of therapeutic agents and as an alternative potential source of collagen (Gunda and Janapala, 2009;Luter and Duckworth, 2010;Pallela et al, 2011a). Our recent reports on H. tenuiramosa, Neopetrosia similis, Petrosia (Xestospongia) testudinaria and Petrosia nigricans also suggest the use of marine sponges as bioindicators and biomonitors for assessing pollution parameters and chemical speciation in any sustainable ecosystem (Rodrigo et al, 1994;Venkateswara Rao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the species distribution patterns, morphological and anatomical variations within the species may influence the production of different kinds of therapeutic agents and as an alternative potential source of collagen (Gunda and Janapala, 2009;Luter and Duckworth, 2010;Pallela et al, 2011a). Our recent reports on H. tenuiramosa, Neopetrosia similis, Petrosia (Xestospongia) testudinaria and Petrosia nigricans also suggest the use of marine sponges as bioindicators and biomonitors for assessing pollution parameters and chemical speciation in any sustainable ecosystem (Rodrigo et al, 1994;Venkateswara Rao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Species description and anatomical structure of sponges are needed to select targeted species to further study the culturing of sponge cells/fragments/whole sponges in situ as well as ex situ for the in vitro synthesis of novel molecules through approached biotechnology (Koopmans et al, 2009;de Caralt et al, 2010). Elemental composition in marine sponges can also be used as biomarkers to assess pollution risks and ecosystem health in the ocean (Venkateswara Rao et al, 2006;Venkateswara Rao et al, 2009). In this paper, biochemical and morphometric variations of three Haliclona species (H. retiderma, H. tenuiramosa and H. cribricutis) of common habitat at Mandapam coast of Gulf of Mannar (GoM), were compared to assess the morphology of these species for our future collections and culturing their cells in vitro to produce secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Value of 1 was set as threshold for all analytes, with results equal or above 1 being considered indicative of bioconcentration. When TE concentration in seawater is included in the study, the BAF are also calculated by dividing the TE sponge's content by the one found in seawater (Padovan et al, 2012;Venkateswara Rao et al, 2009;Batista et al, 2014).…”
Section: Te Bioaccumulation In Spongesmentioning
confidence: 99%
“…The detection of large quantities of TEs in sponges suggests either a high tolerance to diverse type of chemicals or the existence of detoxification systems (Aly et al, 2013). These characteristics make them suitable as a model organisms applied in TEs monitoring projects, and their use has been proposed in several studies (Negri et al, 2006;Venkateswara Rao et al, 2009;Illuminati et al, 2016). Sponges have also been reported as efficient environmental bioremediators of different chemicals or even microbes such as the organochlorine pesticide lindane (Aresta et al, 2015) and the bacterium Escherichia coli (Milanese et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Sponge is animals have pore to having the character of feeder filter so that become habitat to microorganisme to have a nest in its body. Microorganisme have two important role in biological system of sponge, that is first as source of food and both life have symbiosis to either through inter and also intra cellular, [3,6,22] . Some found by sponge type is symbiosis with bacterium, like: Spons Theonella sp,, Surassinoru Melophlus, Callyspongia sp, Ircinia sp, Stylissa Blabeli, Lisoclinum sp, Clathria sp, Jaspis sp, P. nigra, X.Testudinaria and stellifera, [13,15,20] .…”
Section: Theorymentioning
confidence: 99%